Problem Based Learning Model Learning as an Effort to Increase Learning Achievement of Sensor and Transducer Competency - Bujang Rasyid (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2020)
This research was conducted at SMK Negeri 1 Batam in Class XI OIN, where the students' abilities for the sensor and transducer competency material were quite low. The purpose of this classroom action research is to determine whether the Problem Base Learning learning model can improve student achievement. The data collection method is a learning achievement test. The data analysis method is descriptive both for qualitative data and for quantitative data. The results obtained from this study are that participatory discussion can improve student achievement. The results of the learning achievement of students with an average value obtained in Cycle I was 81 with 74% learning completeness. In Cycle II the average value is 92 with learning completeness 87%, so it is found that the Problem Based Learning learning model can improve learning achievement.